Hubungan Simultanitas antara Emisi Gas Rumah Kaca dan Industrialisasi di Indonesia Tahun 1990-2019 - Agustin, Santika Isnaeni; Suhartini, Atik Maratis (Seminar Nasional Official Statistics, 2023)
Industrialization is considered as a strategy for developing countries to improve their economy. However, industrial activities produce greenhouse gas (GHG) emissions that have a negative impact on the environment. If the environment is damaged due to industrial activity, it will also affect the industrial sector because of the depletion of natural resources. This study aims to analyze the simultaneous relationship between GHG emissions and industrialization in Indonesia for 1990-2019. The method used in this study is simultaneous equations model. The result of this study indicates that there is a simultaneous relationship between GHG emissions and industrialization. FDI has a positive effect on GHG emissions, while financial development, economic growth, and industrialization have a negative effect on GHG emissions. Human capital and international trade have a positive effect on industrialization while GHG emissions have a negative effect. Economic growth can be a solution to reduce greenhouse gas emissions if environmental conditions are considered.